SRD5A3‐CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. Issue 12 (2nd August 2016) - Wheeler, Patricia G.; Ng, Bobby G.; Sanford, Laura; Sutton, V. Reid; Bartholomew, Dennis W.; Pastore, Matthew T.; Bamshad, Michael J.; Kircher, Martin; Buckingham, Kati J.; Nickerson, Deborah A.; Shendure, Jay; Freeze, Hudson H.
Abstract : Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N‐glycosylation, O‐mannosylation, C‐mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.